Optimalisasi Penggunaan Teknologi dalam Implementasi Kebutuhan Bahan Ajar BIPA Tingkat Pemula - Maranta, Patrick Fiskhas; B. Widharyanto, B. Widharyanto; Setyaningsih, Yuliana (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
This research is motivated by the phenomenon of Indonesian Language Learning Center (BIPA) that has experienced rapid development in the digital era. However, there are limitations in the development of integrated instructional materials with technology to train speaking skills of beginner-level BIPA learners in Yogyakarta. The research objective is to describe the needs of beginner-level BIPA learners in Yogyakarta in training speaking skills through the use of technology-integrated instructional materials. The research method used a descriptive-qualitative approach. The research data consisted of the results of in-depth interviews with BIPA instructors and the distribution of questionnaires to foreign learners in Yogyakarta. The research findings reveal that BIPA learners have diverse needs for learning materials, concepts, and the integration of technology and information in teaching materials, considering: 1) interactive digital e-books which provide learners in practicing speaking skills, 2) appropriate topic selection, 3) independent use of instructional materials, 4) materials that can accommodate challenges, provide realistic depictions of daily life, and incorporate multimedia variations, 5) diverse learning topics that stimulate learners' cognitive abilities.